2017
DOI: 10.1002/cre2.74
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of implant surface debridement using particle beams at differing air pressures

Abstract: Because implant surface decontamination is challenging, air powder abrasive systems have been suggested as an alternative debridement method. This in vitro study investigated the effectiveness of different powder formulations and air pressures in cleaning implant surfaces and the extent of surface damage. A validated ink model of implant biofilm was used. Sterile 4.1 × 10 mm Grade 4 titanium implants were coated in a blue indelible ink to form a uniform, visually detectable biofilm‐like layer over the implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The publication dates ranged from 1989 to 2018. Seven out of thirteen studies in this group were also presented in Section 3.3.1 . The included studies reported a significant decrease in surface contamination by abrasive powders.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations